Decentralized H controller design for large scale civil structures. - Wang, Yang
Complexities inherent to large-scale modern civil structures pose many challenges in the design of feedback structural control systems for dynamic response mitigation. With the emergence of low-cost sensors and control devices creating technologies from which large-scale structural control systems can deploy, a future control system may contain hundreds, or even thousands, of such devices. Key issues in such large-scale structural control systems include reduced system reliability, increasing communication requirements, and longer latencies in the feedback loop. To effectively address these issues, decentralized control strategies provide promising solutions that allow control systems to operate at high nodal counts. This paper examines the feasibility of designing a decentralized controller that minimizes the ℋ∞ norm of the closed-loop system. ℋ∞ control is a natural choice for decentralization because imposition of decentralized architectures is easy to achieve when posing the controller design using linear matrix inequalities. Decentralized control solutions are investigated for both continuous-time and discrete-time ℋ∞ formulations. Numerical simulation results using a 3-story and a 20-story structure illustrate the feasibility of the different decentralized control strategies. The results also demonstrate that when realistic semi-active control devices are used in combination with the decentralized ℋ∞ control solution, better performance can be gained over the passive control cases. It is shown that decentralized control strategies may provide equivalent or better control performance, given that their centralized counterparts could suffer from longer sampling periods due to communication and computation constraints.
Keywords: H-infinity control; Feedback structural control; Decentralized control; Smart structures